Diagnosis of ulnar-sided wrist pain: a pragmatic approach for the non-specialist. (2nd August 2019) - Sevenoaks, Hannah; Khan, Shah HM; Younis, Fizan
Abstract : Ulnar-sided wrist pain is often unfairly labelled as the 'back pain' of the wrist. This reputation comes from the complexity of diagnosing problems related to this area of the wrist. This article summarizes the anatomy and biomechanics of the wrist and presents a logical approach to diagnosing the aetiology of the pain. The problems are categorised based on the anatomical structure from which the pain arises: either bony, soft tissue-related or arising from nerves or vascular structures. The article also outlines the relevant examination findings and the most appropriate investigation that would yield a diagnosis with any given presentation. A linked article detailing the imaging of ulnar-sided wrist pain is included in this issue (10.12968/hmed.2019.80.8.461 ).